Oxygen-driven relaxation processes in pre-irradiated Ar cryocrystals: Cryocrystals - Savchenko, E.V.; Belov, A.G.; Gumenchuk, G.B.; Ponomaryov, A.N.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Relaxation processes in oxygen-containing Ar cryocrystals pre-irradiated by low-energy electronsare studied with the focus on the role of diffusion controlled atom-atom recombination reaction of oxygen in the relaxation cascades. The results of correlated in real time measurements of thermally stimulated phenomena are presented. The experiments have been performed using activation spectroscopy methods — thermally stimulated exoelectron emission and spectrally resolved thermally stimulated luminescence. Solid evidence of the radiative mechanism of electron detrapping triggering the relaxation cascades is obtained.